Jujube powder supplementation optimized high-moisture alfalfa silage through regulating microbial community - Liu, Zhenyu; Liu, Pengfei; Xie, Nan; Zhi, Jianfei; Wang, Haoyu; Hou, Shenglin; Pang, Xuewei; Wang, Entao; Hu, Guoli; Guo, Lige; Liu, Zhongkuan; Liu, Xiaoyun (Frontiers in Microbiology, 2026)
In order to improve the quality of fresh alfalfa silage, we investigated the effects of jujube powder (JP) addition on the ensiling process of high-moisture alfalfa (75% moisture content) over fermented periods of 1, 5, 15, 30, 45 and 60 days. We evaluated chemical composition, bacterial and fungal community dynamics and diversity, co-occurrence networks, microbial functionality and the ability to restrict pathogenic contamination. Results showed that JP addition optimized key fermentation parameters (pH, lactic acid, volatile fatty acids, and NH3-N) in high-moisture alfalfa, achieving levels comparable to those of traditional wilted alfalfa qualified silage. JP also increased the abundance of beneficial bacteria while suppressing undesirable organisms. A dominant lactic acid bacteria (LAB) combination—Lactobacillus-Pediococcus-Lactococcus was observed, showing strong positive correlations with silage quality indicators (higher qualified LAB counts and NH3-N content, and lower butyric and propionic acid levels). Metabolic pathway analysis revealed that JP supplementation effectively restricted the amino acid metabolism in harmful bacteria while significantly enhancing key carbohydrate-utilization pathways. Notably, D-alanine was unregulated in JP-treated, supporting the survival and function of LAB as the primary fermentation agents. In contrast, the biosynthesis and degradation of branched-amino acids (valine, leucine and isoleucine) remained stable, contributing to better protein preservationl. Furthermore, JP addition helped control plant and animal pathogens and limited saprotrophic activity. In conclusion, by adding JP, the energy- and labor-intensive pre-wilting procedure could be replaced for optimizing the high-moisture alfalfa silage. This work also identifies Lactobacillus-Pediococcus-Lactococcus as a promising microbial combination for future inoculant development.